Perfil de fatores de virulência das Escherichia coli isoladas do útero de vacas holandesas após o parto e sua relação com a microbiota uterina - Bicudo, Luana de Cássia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Bacterial contamination of the uterus after delivery is almost an unanimous event in cows, in which the Escherichia coli (E. coli) is the main micro-organism found. Despite this, the activation of local and systemic defense mechanisms gradually eliminate contaminants throughout the physiological puerperium. However, some bacterias possess virulence factors that facilitate its installation and remain in the host tissue, leading to the development of uterine infections. Although the mechanism is not fully elucidated, it is certified that, the presence of E. coli in the first days postpartum favors the growth of Trueperella pyogenes in a later period, bacteria often associated with uterine infection. Thus, aimed to establish the dynamics and profile of uterine microbiota relating the virulence factors of E. coli isolated from the uterus of cows 24 hours after calving, with the bacterial presence in the uterine environment in the second postnatal week. The study was conducted on 75 Holstein cows with normal delivery and postpartum without complications. After 24 hours of parturition (Moment 1), gynecological evaluation was performed by rectal palpation, observed staining of the vaginal mucosa and measurement of rectal temperature. Samples of secretion loquial were collected aseptically of these animals, aiming the microbiological culture, antibiogram and uterine cytology. The postpartum period was uneventful and monitored for changes in the reproductive and productive sphere. On the 14th day postpartum (Time 2), the same procedures were were performed, apart from transrectal ultrasonography. Blood samples were collected at both moments, to characterize the phagocytic ability of neutrophils by the nitroblue tetrazolium test (NBT) stimulated (S) and unstimulated (US) and hemogram. In E. coli isolates were investigated different genes associated with virulence factors (VF) by PCR. Rapid uterine involution, characterized by diameter of the ...

A contaminação bacteriana do útero após o parto é um evento quase unânime em vacas, em que a Escherichia coli (E. coli) é o principal micro-organismo encontrado. Apesar disto, a ativação de mecanismos de defesa local e sistêmica eliminam gradualmente os contaminantes ao longo do puerpério fisiológico. Porém, algumas bactérias possuem fatores de virulência, que facilitam sua instalação e permanência no tecido hospedeiro, propiciando o desenvolvimento de infecções uterinas. Embora o mecanismo não esteja completamente elucidado, certifica-se que a presença de E. coli nos primeiros dias pós-parto favorece o crescimento de Trueperella pyogenes num período mais tardio, bactéria frequentemente associada à infecção uterina. Com isto, objetivou-se estabelecer a dinâmica e perfil da microbiota uterina relacionando os fatores de virulência das E. coli isoladas do útero das vacas, 24 horas após a parição, com a presença bacteriana no ambiente uterino na segunda semana pós-parto. O estudo foi conduzido em 75 vacas holandesas preto e branca (HPB) com parto e puerpério isento de complicações. Decorridas 24 horas do parto (Momento 1) foi realizada avaliação ginecológica através da palpação retal, observada a coloração da mucosa vaginal e aferição da temperatura retal. Destes animais foram coletadas, em condições de assepsia, amostras da secreção loquial visando-se o cultivo microbiológico, antibiograma e a citologia uterina. O período pós-parto foi monitorado quanto às intercorrências e alterações da esfera reprodutiva e produtiva. No 14º dia pósparto (Momento 2), foram realizados os mesmos procedimentos, além da ultrassonografia transretal. Amostras de sangue foram coletadas, em ambos os momentos, para a caracterização da capacidade fagocítica dos neutrófilos pelo teste do nitroblue tetrazolium (NBT) estimulado (ES) e não estimulado (NE) e realização de hemograma. Nas E. coli isoladas foram ...
Profile of virulence factors of Escherichia coli isolated from the uterus of Holstein cows after calving and their relationship with the uterine microbiota
Keywords: Vaca - Doenças; Escherichia coli; Puerperio; Virulencia (Microbiologia); Utero - Infecções; Microbiota